Electronic legislative initiative as a Tool to improve Citizens’ Public activity in Cyberspace: Common issues in the BriCs Countries, europe and the russian Federation - K. Ivanova (BRICS Law Journal, 2019)
Around the world, parliaments, governments, civil society organizations and even individual parliamentarians are taking measures to make the legislative process more participatory. A key instrument of such measures is e-democracy. In the 1980s, a number of pilot projects on electronic voting and online discussions were introduced. However, only since 2000, with the active development of the Internet, has considerable interest in utilizing electronic initiatives to advance democracy emerge. Today, researchers warn that despite all the talk about “e-democracy,” the circle of actual decision makers is likely to remain as small as it has been heretofore. In this article, the author analyzes the pros and cons of electronic initiatives in the BRICS countries, Europe and the Russian Federation, and provides practical information for improvement. The author suggests that the next step needed to improve civil activity in filing legislative initiatives is the application of a regular mechanism to establish the possibility of organizing the process of civil legislative initiative nomination and the collection of signatures in electronic form, in particular via the Internet, with the possible use of crowd sourcing technologies.